2008
DOI: 10.1111/j.1365-2648.2008.04834.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking ability of new graduate and experienced nurses

Abstract: Aim-This paper is a report of a study to identify critical thinking learning needs of new and experienced nurses.Background-Concern for patient safety has grown worldwide as high rates of error and injury continue to be reported. In order to improve patient safety, nurses must be able to recognize changes in patient condition, perform independent nursing interventions, anticipate orders and prioritize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 21 publications
5
94
0
12
Order By: Relevance
“…Nurses should be able to detect changes in the patient's condition and carry out nursing interventions, anticipate, and precede the orders. This function requires the ability to think critically, solve problems, and communicate effectively (Fero et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Nurses should be able to detect changes in the patient's condition and carry out nursing interventions, anticipate, and precede the orders. This function requires the ability to think critically, solve problems, and communicate effectively (Fero et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Survey findings published in 2003 revealed that approximately 49% of newly licensed registered nurses were involved in patient-care errors, with 75% indicating involvement with medication errors [14] . Results from a study that compared clinical competence between new graduate nurses and experienced nurses showed that new graduate nurses were less likely to meet clinical expectations than experienced nurses [15] . Incompetent new graduate nurses may cause serious negative patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Nos résultats appuient cette idée et coïncident avec ceux de l'étude antérieure [1] . D'après Fero et al [4] , la plupart des études montrent une progression dans le développement des capacités de pensée critique des étudiantes infirmières selon leur niveau de formation. De plus, selon Smith [37] , la transition des étudiants se fait à travers une série de stades de développement du RCI, de novice à experte.…”
Section: Discussionunclassified
“…Pour les infirmières, le raisonnement clinique infirmier (RCI) est vu comme une compétence fondamentale pour l'exercice de leur profession et comme un défi prioritaire de leur formation [3] . Développer et évaluer des stratégies éducatives pour aider les infirmières à développer leur RCI pourrait contribuer à rendre les soins plus sûrs pour les patients [4] . Puisque l'évaluation a un impact important sur les stratégies d'apprentissage des étudiants [5] , il paraît essentiel de développer des instruments d'éva-luation valides et fidèles pour identifier les problèmes de RCI dans une approche diagnostique.…”
Section: Introductionunclassified